BIRC3 alterations in chronic and B-cell acute lymphocytic leukemia patients - Alhourani, Eyad (2016)
Deletions within chromosome 11q22-23, are considered among the most common chromosomal aberrations in chronic lymphocytic leukemia (CLL), and are associated with a poor outcome. In addition to the ataxia telangiectasia mutated (ATM) gene, the baculoviral IAP repeat-containing 3 (BIRC3) gene is also located in the region. BIRC3 encodes a negative regulator of the non-canonical nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) protein. Disruption of BIRC3 is known to be restricted to CLL fludarabine-refractory patients. The aim of the present study was to determine the frequency of copy number changes of BIRC3 and to assess its association with two known predictors of negative CLL outcome, ATM and tumor protein 53 (TP53) gene deletions. To evaluate the specificity of BIRC3 alterations to CLL, BIRC3 copy numbers were assessed in 117 CLL patients in addition to 45 B-cell acute lymphocytic leukemia (B-ALL) patients. A commercially available multiplex ligation dependent probe amplification kit, which includes four probes for the detection of TP53 and four probes for ATM gene region, was applied. Interphase-directed fluorescence in situ hybridization was used to apply commercially available probes for BIRC3, ATM and TP53. High resolution array-comparative genomic hybridization was conducted in selected cases. Genetic abnormalities of BIRC3 were detected in 23/117 (~20%) of CLL and 2/45 (~4%) of B-ALL cases. Overall, 20 patients with CLL and 1 with B-ALL possessed a BIRC3 deletion, whilst 3 patients with CLL and 1 with B-ALL harbored a BIRC3 duplication. All patients with an ATM deletion also carried a BIRC3 deletion. Only 2 CLL cases possessed deletions in BIRC3, ATM and TP53 simultaneously. Evidently, the deletion or duplication of BIRC3 may be observed rarely in B-ALL patients. BIRC3 duplication may occur in CLL patients, for which the prognosis requires additional studies in the future. The likelihood that TP53 deletions occur simultaneously with BIRC3 and/or ATM aberrations is low. However, as ATM deletions may, but not always, associate with BIRC3 deletions, each region should be considered in the future diagnostics of CLL in order to aid treatment decisions, notably whether to treat with or without fludarabine.